PERSEPSI DAN SIKAP TERHADAP KEPUTUSAN PEMBELIAN PRODUK PANGAN FUNGSIONAL PADA GENERASI MILENIAL - DEWI NUSRANINGRUM; TRI MAYANG MEKAR; SEKAR WULAN PRASETYANINGTYAS (Jurnal Bisnis dan Akuntansi, 2021)
Functional food consumption is one of the trends in the World food market industry, along with increasing public awareness for healthy living. But the market share of functional food is still very small when compared to the food and beverage market as a whole. The study aims to determine how the perception and attitude of millennials influence the consumption of functional food. Data retrieval is done by using online poll to 110 respondents aged 13 to 32 years residing in the area of Jakarta, Bogor, Depok and Tangerang. Data analysis techniques using Structural Equation Modeling. Testing proved that the consumer perception of millennials gave a positive and significant influence on the purchasing decisions of functional food. Millennials have the perception that functional food is attractive, and in the act, they want functional food to be a part of consumption. By knowing how perception and attitude influence purchasing decisions, it is hoped to help the industry to devise the right business strategy.